Prenatal methadone exposure selectively alters protein expression in primary motor cortex: Implications for synaptic function - Haggerty, David L.; Grecco, Gregory G.; Huang, Jui-Yen; Doud, Emma H.; Mosley, Amber L.; Lu, Hui-Chen; Atwood, Brady K. (Frontiers in Pharmacology, 2023)
As problematic opioid use has reached epidemic levels over the past two decades, the annual prevalence of opioid use disorder (OUD) in pregnant women has also increased 333%. Yet, how opioids affect the developing brain of offspring from mothers experiencing OUD remains understudied and not fully understood. Animal models of prenatal opioid exposure have discovered many deficits in the offspring of prenatal opioid exposed mothers, such as delays in the development of sensorimotor function and long-term locomotive hyperactivity. In attempt to further understand these deficits and link them with protein changes driven by prenatal opioid exposure, we used a mouse model of prenatal methadone exposure (PME) and preformed an unbiased multi-omic analysis across many sensoriomotor brain regions known to interact with opioid exposure. The effects of PME exposure on the primary motor cortex (M1), primary somatosensory cortex (S1), the dorsomedial striatum (DMS), and dorsolateral striatum (DLS) were assessed using quantitative proteomics and phosphoproteomics. PME drove many changes in protein and phosphopeptide abundance across all brain regions sampled. Gene and gene ontology enrichments were used to assess how protein and phosphopeptide changes in each brain region were altered. Our findings showed that M1 was uniquely affected by PME in comparison to other brain regions. PME uniquely drove changes in M1 glutamatergic synapses and synaptic function. Immunohistochemical analysis also identified anatomical differences in M1 for upregulating the density of glutamatergic and downregulating the density of GABAergic synapses due to PME. Lastly, comparisons between M1 and non-M1 multi-omics revealed conserved brain wide changes in phosphopeptides associated with synaptic activity and assembly, but only specific protein changes in synapse activity and assembly were represented in M1. Together, our studies show that lasting changes in synaptic function driven by PME are largely represented by protein and anatomical changes in M1, which may serve as a starting point for future experimental and translational interventions that aim to reverse the adverse effects of PME on offspring.